Temporal analysis of climatic factors influencing silkworm disease incidences in commercial sericulture crops of West Bengal, India (2018–2024) - Mihir Rabha; T. N. Ethungbeni; K. Rahul; Khasru Alam; M. Maheswari (Journal of Basic and Applied Zoology)
Abstract Background Mulberry sericulture in West Bengal is significantly impacted by various silkworm diseases, including Grasserie, Flacherie, Muscardine, and Pebrine. This study investigates the influence of weather parameters on the occurrence of these diseases. Results The findings indicate that Grasserie and Flacherie are the most prevalent diseases, occurring throughout the year. Over the past six years (2018–2024), the highest incidence of Grasserie was recorded during the Shravani (8.37%) and Bhaduri (7.18%) crops, while the highest incidence of Flacherie occurred during the Shravani (3.4%) and Bhaduri (5.08%) crops. Both diseases showed higher incidences during the rainy and summer seasons. The highest incidence of Muscardine was observed during the Falguni (3.84%) crop, followed by the Agrahayani (2.22%) crop. Correlation analysis revealed a strong positive relationship between the incidences of Grasserie and Flacherie with minimum temperature and maximum relative humidity (RH). Conversely, Muscardine incidence showed a strong negative correlation with minimum temperature and maximum RH. Conclusion Overall, the study highlights the significant impact of weather fluctuations, particularly minimum temperature and maximum RH, on the multiplication of silkworm pathogens and the eventual occurrence of silkworm diseases.